2022
DOI: 10.1136/bmjsit-2022-000140
|View full text |Cite
|
Sign up to set email alerts
|

Survival, reintervention and surveillance reports: long-term, centre-level evaluation and feedback of vascular interventions

Abstract: The combination of registry and administrative claims data have facilitated research and quality improvement efforts. Using Vascular Quality Initiative (VQI) registry data and Medicare claims we have generated centre-specific survival, reintervention and surveillance reports which benchmark participating centres’ performance to the VQI as a whole and to published guidelines. In 2021, we distributed these reports to 303 participating centres. These reports offer an opportunity for centres to evaluate their perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Claims-linked data have been shown to accurately predict trial-adjudicated deaths, 16 and Medicare data have been demonstrated to capture 30% more deaths than VQI alone. 17 Patients were followed for 90 days after the index procedure, until December 31, 2019, or until death, whichever occurred first.…”
Section: Methodsmentioning
confidence: 99%
“…Claims-linked data have been shown to accurately predict trial-adjudicated deaths, 16 and Medicare data have been demonstrated to capture 30% more deaths than VQI alone. 17 Patients were followed for 90 days after the index procedure, until December 31, 2019, or until death, whichever occurred first.…”
Section: Methodsmentioning
confidence: 99%